Oppositional brand choice: Using brands to respond to relationship frustration1. Issue 2 (20th October 2016) - Brick, Danielle J.; Fitzsimons, Gavan J.
Abstract: Within close relationships individuals feel a variety of emotions toward their partner, often including frustration. In the present research we suggest a novel way in which individuals respond to frustration with their partner is through their choice of brands. Specifically, we introduce the concept of oppositional brand choice, which we define as occurring when individuals choose a brand for themselves that is in opposition to the one they believe their partner prefers. Importantly, we posit that this effect is specific to individuals who are low in relationship power. Across several studies, including a subliminal priming lab study, we find that people who are lower in relationship power and are frustrated with their partner make significantly more oppositional brand choices. Further, we find that this effect is not due to a shift in underlying brand preferences. The current research has implications for theory in brand choice, close relationships, emotions, and social power.